Dispersion Optimization in GeO2-doped Silica Photonic Crystal Fibers with Circular Lattice - Thuy Nguyen Thi (Majlesi Journal of Electrical Engineering)
In this paper, we analyze the dispersion properties of photonic crystal fiber with the core replaced by a composite of 85% SiO2-15% GeO2. The air hole's radii of the layers in the cladding are designed differently to improve the dispersion and nonlinear properties of the fibers. Both anomalous and all-normal dispersions have been optimized. Based on numerical simulation results, two optimal structures (d1/É = 0.4, É = 0.9 µm and d1/É = 0.45 and É = 1.0 µm) are proposed with a very small dispersion value of 0.298 ps/ nm.km and â0.311 ps/nm.km at the pump wavelength of 1.53 µm and 0.985 µm, respectively. The high nonlinear coefficient, small effective mode area, and very low attenuation of about 10â7 dB/m at the pump wavelength are also favorable conditions for the application of broad-spectrum supercontinuum with low peak power. The proposed fibers can be new supercontinuum sources that effectively replace glass core fibers.